2007
DOI: 10.1177/1721727x0700500201
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response in Infective Endocarditis

Abstract: Endocarditis remains a devastating disease with a high mortality despite timely diagnosis and treatment. The mainstays of treatment include appropriate antibiotics and when indicated, removal of the septic focus. This sounds extremely simple and belies the necessity for a sophisticated multidisciplinary approach to its treatment, the success of which depends not just on the right antibiotic at the right dosage via the right portal, but also on a profound understanding of the inflammatory and infective pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…Subsequent analysis showed that the number of crises was associated with an altered alert status and/or to a mental slowing, while the length of the crisis (the critical period) was associated with memory alterations. [42][43][44][45][46] Again, only in the presence of frequent crises is there an alteration of mental alertness, and only during a crisis of threshold duration can we observe a deterioration of memory, as found in other studies. 11,16 The effect of the crisis is not independent of the type of epilepsy.…”
Section: Discussionsupporting
confidence: 88%
“…Subsequent analysis showed that the number of crises was associated with an altered alert status and/or to a mental slowing, while the length of the crisis (the critical period) was associated with memory alterations. [42][43][44][45][46] Again, only in the presence of frequent crises is there an alteration of mental alertness, and only during a crisis of threshold duration can we observe a deterioration of memory, as found in other studies. 11,16 The effect of the crisis is not independent of the type of epilepsy.…”
Section: Discussionsupporting
confidence: 88%
“…Fibrinogen is elevated in HD patients, influences arterial remodelling, and correlates positively with CIMT (29). Higher concentrations of these substances may be involved in the atherogenic inflammatory process in predialysis and HD patients (46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…These concepts support the conclusion that IgE can signal the transition from inflammatory cell rolling to cell arrest [35] . We believe that there are some correlations between HUCMC-induced IL-8 and tryptase release since it has been reported that blocking tryptase reduces IL-8 significantly, a phenomenon not related with histamine production [31,[53][54][55][56] . However, more studies on IL-8 production by mast cells in vivo and in vitro are required to clarify the specificity of its proinflammatory effect.…”
Section: Discussionmentioning
confidence: 99%